GLC: Delivery through shared responsibility - TAN, Kar Way (Institutional Knowledge at Singapore Management University, 2017)
Andy Smith is the Transport Excellence Manager (Asia-Pacific) at GLC, a leading global logistics services company. In April 2016, GLC inaugurated the GLC Hub in Singapore, which is expected to boost cargo volume in Asia-Pacific. However, Smith faces issues further down the supply chain due to problems with road freight vendors. GLC utilises a hub-and-spoke method to transport cargo. Last mile deliveries are typically outsourced to small local transportation providers in the Asia-Pacific region who would complete the delivery by road. These vendors are usually small companies with only a few vehicles. They do not always make the best decisions about their operations, (e.g., deciding the type and combination of vehicles to be used in the fleet), or the type of resources (such as fuel, equipment on board) to be used. This inefficiency results in vendor bankruptcies and subsequent disruptions to GLC’s delivery obligations. Smith wanted to devise a long-term solution to help his vendors manage their operations. He decided it would be best to help address their business needs and enable the vendors to make better managerial decisions. He started collating data in an Excel spreadsheet, but it soon became apparent that the spreadsheet was not ideal. He then considered other solutions such as developing a common platform, using Software-as-a-Service (SaaS) visual analytics online tools or creating a customised application. He wanted a tool that would ideally allow vendors to analyse their financial health over a period of time, and perform scenario analysis to aid their decision-making.